The impact of temperature patterns during storage of Scots pine and Norway spruce seeds on their germination and fungal infection rates - M. A. Nikolaeva; E. Yu. Varentsova; G. F. Safina (Труды по прикладной ботанике, генетике и селекции)
Relevance of the study. One of the ways to maintain the genetic diversity of forest-forming species is to preserve highquality seed material ex situ. However, the relationship between the diversity of pathogenic mycobiota and the duration and methods of forest tree seed storage remains underexplored. The results of research into this problem can be used in forest seed production and forest phytopathology.Materials and methods. For our study we used seeds of Рinus sylvestris L. and Picea abies (L.) Karst. of the orthodox type, harvested in the period of 1996–2011 and stored under different temperatures: +20°С, +4°С, –18°С, and in liquid nitrogen vapor (–182°С) since 2011. Prior to their storage, seed samples were dried to a moisture content of 4.2–4.4% and hermetically packed. Seed germination was tested before and after three, five and eight years of storage, following GOST 13056.6-97 standards. The level of seed infection and the composition of pathogenic fungi were assessed.Results. After eight years of storage at +20°С, pine and spruce seed germination capacity decreased by 13–60%, depending on the year of harvesting. Seed storage at –18°С and –182°С allowed us to prevent seed infection and preserve seed viability. In most cases, the germination energy and germination capacity were negatively correlated with the level of seed infection. The diversity of pathogenic (mold) fungi on the surface of seeds was represented by ten genera; the most common were saprotrophs: Aspergillus P. Micheli, Penicillium Link, Rhizopus Ehrenb., Scopulariopsis Bainier.Conclusion. At the present stage of research, the success of seed storage at low and ultralow temperatures was demonstrated. We recommend cryopreservation for the long-term storage of improved and valuable seeds.